PENGARUH EMOTIONAL CHECK-IN DALAM MENDUKUNG REGULASI EMOSI ANAK USIA DINI DI TK ISLAM AR-RAHMAT - Nur Ayesha, Fidhea; Syarif Hidayatullah, M. Arif; Maulana, M. Azka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the limited emotional regulation ability among early childhood students at TK Islam Ar-Rahmat, indicated by behaviors such as hitting peers, prolonged crying, and the use of harsh language. This study aimed to: (1) describe children's emotional regulation before emotional check-in; (2) describe children's emotional regulation after emotional check-in; and (3) analyze the effect of emotional check-in on early childhood emotional regulation. A quantitative approach with true experimental design (pretest-posttest control group design) was used. The sample consisted of 20 children aged 5–6 years, divided into an experimental group (n=10) and a control group (n=10). The instrument was an emotional regulation observation sheet of 8 valid items (from 12 tested) on a 1–4 scale. Data were analyzed using the Shapiro-Wilk test, Levene's Test, Independent Sample t-Test, and Cohen's d effect size. Results showed the experimental group's mean posttest score (2.980) was significantly higher than the control group (2.480). The Independent Sample t-Test yielded t = −2.751, Sig. (2-tailed) = 0.013 < 0.05, so H₀ was rejected. Cohen's d = −1.231 indicated a large effect. Therefore, emotional check-in significantly affects emotional regulation of early childhood students at TK Islam Ar-Rahmat.